Measuring the Relationship Between The Indicators of The Optimal Level of Foreign Reserves and The Window for Selling Foreign Currency in Iraq for the period (2004-2021) - salim Yahya Hassan, Muthana; Mahdi Abbas Al-Birmani , Salah (Journal of Economics and Administrative Sciences, 2024)
Foreign reserves are important in supporting the local currency, as the Iraqi economy maintained an optimal level of foreign reserves and the(CB) contributed to sterilizing the money supply, confronting the increasing spending of the Ministry of Finance, and maintaining the stability of the local currency exchange rate, as the study aimed to analyze the impact The window on inflation rates, which is one of the direct tools used by monetary policy. The problem of the study is that rentier economies suffer from weak transmission and effectiveness of traditional channels, so the window for selling foreign currency must be followed. The study concluded that the (CBI) maintained an optimal level of foreign reserves, The monetary sterilization mechanism achieved positive and acceptable results despite the many increases in government spending, and the Central Bank was able to eliminate the pluralism in exchange rates and gradually reduce inflation rates. After inflation was recording an increase of 53.1% in 2006, the Central Bank was able To reduce it to (6%) in (2021) And the results of the econometric analysis showed that there is a direct relationship and cointegration between foreign reserves and the window for selling foreign currency, as the value of (Bounds test) reached (8.1621). Paper type: Research paper.